Plasmonic Coupling in Er3+:Au Tellurite Glass - Osorio, Sergio P. A.; Rivera, Victor A. Garcia; Nunes, Luiz Antonio O.; Marega, Euclydes; Manzani, Danilo [UNESP]; Messaddeq, Younes [UNESP] (Springer, 2012)
In this paper, we report on luminescence and absorbance effects of Er+3:Au-doped tellurite glasses synthesized by a melting-quenching and heat treatment technique. After annealing times of 2.5, 5.0, 7.5, and 10.0 h, at 300 A degrees C, the gold nanoparticles (GNP) effects on the Er+3 are verified from luminescence spectra and the corresponding levels lifetime. The localized surface plasmon resonance around 800 nm produced a maximum fluorescence enhancement for the band ranging from 800 to 840 nm, corresponding to the transitions H-4(11/2) -> aEuro parts per thousand I-4(13/2) (805 nm) and S-4(3/2) -> aEuro parts per thousand I-4(13/2) (840 nm), with annealing time till 7.5 h. The measured lifetime of the levels H-4(11/2) and S-4(3/2) confirmed the lifetime reduction due to the energy transfer from the GNP to Er+3, causing an enhanced photon emission rate in these levels.
Keywords: Gold nanoparticles; Localized surface plasmon resonance; Fluorescence enhancement; Tellurite glass